Strengthening internal controls to reduce fraud in U.S. financial institutions: Enhancing financial integrity and public trust - Abdoulie K Darboe (Radiant Journal of Business & Sustainability, 2026)
Financial fraud remains a constant and evolving threat to U.S. financial institutions, damaging market integrity, diminishing public trust, and causing significant economic losses. Internal control systems serve as the first line of defense against such fraud, yet many institutions still face control failures that allow internal and external schemes to thrive. Despite comprehensive regulatory requirements and compliance measures, fraud incidents persist, highlighting ongoing weaknesses in the design and execution of internal controls. This underscores the need for stronger, technology-driven prevention strategies. This research analyzes the effectiveness of internal control systems in preventing and detecting fraud in U.S. financial institutions. It proposes an integrated framework combining governance mechanisms, risk assessment, technological advancements, and human capital development to improve fraud deterrence. The study uses an applied qualitative approach to systematically review and compare evidence from academic journals, government reports, banking regulations, and industry publications. The evidence indicates that successful fraud prevention requires a multi-layered strategy incorporating robust corporate governance, comprehensive risk assessment, segregation of duties, ongoing monitoring, and sophisticated data analytics. Technology-based solutions, especially machine learning and artificial intelligence, typically surpass traditional detection methods. Additionally, corporate governance elements, such as the effectiveness of audit committees and board oversight, are vital in ensuring the effectiveness of internal controls. Based on these findings, financial institutions should enhance their governance frameworks, implement risk-focused internal controls, invest in ongoing monitoring technologies, upgrade employee training programs, and foster stronger collaborations with regulators. Collectively, these measures establish robust fraud prevention systems capable of safeguarding institutional integrity and maintaining public trust. Keywords: Internal Controls, Fraud Prevention, Fraud Detection, Corporate Governance, COSO Framework, Financial Institutions, Data Analytics, Machine Learning, Regulatory Compliance, Audit Committees.